MENGGALI NILAI-NILAI PENDIDIKAN DALAM MISI KARASULAN - Dwi Priyanto (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2012)
Abstract : That Allah sent messengers to mankind in the mission apostolate is in order to convey moral values to guide people towards the path of salvation and happiness of life. The tasks of the apostle thus place them as educators in the midst of the people. They are the chosen people who prepared the required competence to the mission of their duties so that they succeed in carrying out his apostolic mission. Information submitted in Qur’an and the explanation given by the historian about the acts of the apostles and the problems they faced are not only as knowledge or discourse, but to get the messages moral teachings contained therein, as well as be used as an afterthought to the possibility of their application in the next future. Thus such belief is expected to lead to the psychological impact of educative for mankind. There are so much educational values that can be extracted from the apostolic mission discourse that we get a variety of inspiration related to aspects of educational measures to be implemented in education today. Key Words: Values Education, Mission, Apostolic.